2023
DOI: 10.1111/jog.15632
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different postoperative adjuvant therapies on the survival of early‐stage cervical cancer patients with one intermediate‐risk factor: A multicenter study of 14 years

Abstract: Objective To compare survival outcomes of different postoperative adjuvant therapies (PATs) for early‐stage cervical cancer (ECC) patients with one intermediate‐risk pathological factor (IPF). Methods A total of 2889 patients with stage IA1 to IIA2 cervical cancer were included in this study. Three PAT groups were identified, namely a no adjuvant therapy (NAT) group (n = 773), an adjuvant radiotherapy/chemoradiotherapy (ART) group (n = 1648) and an adjuvant chemotherapy (ACT) group (n = 468). Kaplan–Meier anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The primary objective of adjuvant therapy extends beyond controlling local recurrence to also aiming at reducing the risk of distant metastases. However, while adjuvant pelvic radiation may lower the incidence of local recurrences [ 12 ], it is not effective in preventing distant metastases [ 13 ], which contributes to the limited impact of postoperative RT on overall survival [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The primary objective of adjuvant therapy extends beyond controlling local recurrence to also aiming at reducing the risk of distant metastases. However, while adjuvant pelvic radiation may lower the incidence of local recurrences [ 12 ], it is not effective in preventing distant metastases [ 13 ], which contributes to the limited impact of postoperative RT on overall survival [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, adjuvant radio(chemo) therapy is increasingly recommended for these patients, but its actual efficacy is still controversial and designing tailored therapeutic schedules is extremely challenging ( 16 ). A retrospective study has found adjuvant radiotherapy/chemoradiotherapy failed to provide significant benefits for OS or DFS in early-stage CC patients with one intermediate-risk factor ( 17 ). For a considerable proportion of early-stage CC patients with pelvic lymph node metastases, adjuvant radiotherapy concurrent with chemotherapy failed to provide superior survival benefits as compared with chemotherapy alone ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent nationwide retrospective study (n=6192) has suggested adjuvant therapies should be cautiously recommended in some of these subpopulation, where adjuvant chemotherapy may be effective in patients with large tumors (31). Another retrospective study has found no significant correlation between postoperative adjuvant therapies and clinical outcomes in stage IA1 to IIA2 CC patients with one intermediate-risk factor (17). However, the opposite result was observed in a study that proved stage I-IIA CC patients could benefit from postoperative chemotherapy or radiotherapy or sequential chemotherapy and radiotherapy (32).…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the adverse events associated with radiation therapy following radical surgery such as lower-limb lymphedema, urinary disturbance, bowel obstruction, sexual dysfunction, and mental health issues caused by the lasting issues of other adverse events, and these are frequently more severe than the extent of adverse events associated with chemotherapy ( 10 ). Additionally, the efficacy of adjuvant chemotherapy has been increasingly reported ( 6 , 10 , 29 ). Additionally, one of the advantages of using chemotherapy as adjuvant therapy is that if radiation therapy is not performed as adjuvant therapy during the primary treatment, it can be used if loco-regional recurrence occurs ( 4 , 10 , 30 ).…”
Section: Discussionmentioning
confidence: 99%